A articulação docente na valorização dos conhecimentos prévios: uma abordagem a partir das contribuições de Piaget, Ausubel e Freire - GUIMARÃES, Maria do Socorro da Silva (2019)
The present research is a work of conclusion of course and aims to investigate the contributions of Piaget, Ausubel and Freire in the construction of the knowledge coming from the school, based on the valuation of the previous knowledge well articulated by the teachers. I discussed how this construction takes place in the view of these authors and what the role of the teacher in this process is. Some differences between traditional teaching and constructivist teaching will also be pointed out; analyzing some counterpoints established during the research in a primary school in the city of São Francisco do Pará. The qualitative approach was chosen and has as instrument of data collection the semi structured interview. As a result, we highlight: teachers need to better articulate such knowledge in their planning for a meaningful learning of students, despite knowing of your importance.